Investigating the use of mobile instant messaging-facilitated 5E-flipped learning: a two-stage study. (7th April 2020) - Tang, Ying; Hew, Khe Foon; Lo, Chung Kwan
Despite the worldwide popularity of flipped learning, we understand little about how to coherently structure a flipped class with appropriate communication services to engage students. This two-stage study examines in flipped learning context, how students perceived learning guided by the 5E design model (engagement-exploration-explanation-elaboration-evaluation), and how different technologies impacted the learning experience. We first reported a multiple-case study on how students felt about the 5E model-based flipped learning, facilitated by mobile instant messaging (MIM) tools. We then conducted a comparative study to investigate how students felt about using either MIM or a threaded asynchronous forum for discussion. The results suggested that 92% of participants found flipped learning more engaging and 81% reported that flipped learning gave them more time to discuss or solve problems. Most students welcomed using MIM for flipped learning, but online forum was still preferred for academic discussions. Possible reasons and suggestions for future research are discussed.